CRITICAL EVALUATION OF HOW WELL PLACED AMAZON IS TO SUSTAIN ITS HISTORICAL IN ONLINE RETAILING - Emeka Izogo and Johnson Ubaka Ozo, Ernest (British Journal of Marketing Studies, 2015)
E-commerce has staged a stay in modern day businesses and the retail sector is not an exception. As such, competing in the 21st century market without online presence is simply unthinkable because the Internet has offered organizations an entirely new and efficient way of delivering value to customers and achieving sustainable competitive advantage (SCA). This paper therefore, is essentially a mapping exercise that critically examined how Amazon has deployed the Internet to develop a business strategy that is changing the face of retailing and driving the company towards SCA. We first identified the key factors responsible for Amazon’s current success and thereafter, presented some critical issues that the company should watch if it wants to outlast its critiques. Drawing from basic financial analysis, the resource-based view (RBV) as well as SWOT diagnosis, we argue that although Amazon generates astounding sales volume on yearly basis, the proportion of these sales that actually translates to profits is very infinitesimal because of the company’s business model and rising operational costs. Interestingly too, we found that Amazon is yet to do excellent customer profiling despite its good technologies. We argue that whilst it is too early to conclude that Amazon will hit a plateau very soon, the company’s long-term vision, business model, customer-centric philosophy, continuous product/process innovation and pool of unique employees are strategic resources that were found to be great sources of SCA. In the light of the abovementioned and coupled with the predictions that e-commerce will continue to grow, we reinforce that Amazon stands a great chance of putting the sharp-end of its business at the cutting-edge if it deploys resources more efficiently, keep its debt financing within plausible limits, reduce rising operating costs, examine working conditions in its warehouses and do better customer profiling.